Access to Jobs, Economic Opportunities, and Education in Rural Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Rural areas face unique challenges in providing connectivity and access to essential goods and services, including but not limited to jobs, education, health care, and social services. NCHRP Research Report 1059: Access to Jobs, Economic Opportunities, and Education in Rural Areas, from TRB's National Cooperative Highway Research Program, presents a guide to defining and addressing the unique accessibility challenges in rural communities. Supplemental to the report are decision-support tools that can be used to facilitate agency assessment of accessibility needs within their service jurisdictions and to recommend methods for addressing accessibility needs in a decision-making context and an implementation plan that describes expected challenges and opportunities in the implementation of research findings.
Keywords: Transportation and Infrastructure

Highway Safety Behavioral Strategies for Rural Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Rural roads have a higher risk of fatality or serious injury than urban roads due to factors such as varying terrain, wildlife, and long distances between services. BTSCRP Web-Only Document 4: Highway Safety Behavioral Strategies for Rural Areas, from TRB's Behavioral Transportation Safety Cooperative Research Program, documents the overall research effort that produced BTSCRP Research Report 8: Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide. Supplemental to the document is a PowerPoint presentation that outlines the project.
Keywords: Transportation and Infrastructure

Assessing the Impacts of Right-Turn Lanes on Rural and Suburban Highways - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Dedicated right-turn lanes (RTLs) are typically installed on highways and arterial roads at intersections to improve motor vehicle traffic operations and avoid high-speed rear-end crashes. However, vehicles decelerating or queued in an RTL may obstruct the view of drivers turning onto or crossing the major road from the minor road at stop-controlled intersections where operating speeds are relatively high on the major road. NCHRP Research Report 1062: Assessing the Impacts of Right-Turn Lanes on Rural and Suburban Highways, from TRB's National Cooperative Highway Research Program, presents a state-of-the-art update to enhance the safety performance of RTLs on rural and suburban roads. Supplement to the report is a sightline tool dataset.
Keywords: Transportation and Infrastructure

Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Roadway fatalities and serious injuries are a significant public health concern in rural and tribal settings. Creating a coalition of interested individuals is part of the Safe System Approach that addresses the high rates of these fatalities and serious injuries. BTSCRP Research Report 8: Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide, from TRB's Behavioral Transportation Safety Cooperative Research Program, details this approach, which includes strategies for safer people, safer roads, safer vehicles, safer speeds, and post-crash care. Supplemental to the report are BTSCRP Web-Only Document 4: Highway Safety Behavioral Strategies for Rural Areas and a video that explains how to create a logic model.
Keywords: Transportation and Infrastructure

Achieving Whole Health: A New Approach for Veterans and the Nation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Whole health is physical, behavioral, spiritual, and socioeconomic well-being as defined by individuals, families, and communities. Whole health care is an interprofessional, team-based approach anchored in trusted relationships to promote well-being, prevent disease, and restore health. It aligns with a person's life mission, aspiration, and purpose. It shifts the focus from a reactive disease-oriented medical care system to one that prioritizes disease prevention, health, and well-being. It changes the health care conversation from "What’s wrong with you?" to "What matters to you?"The Department of Veterans Affairs (VA), the Samueli Foundation, and the Whole Health Institute commissioned the National Academies of Sciences, Engineering, and Medicine to establish a committee to provide guidance on how to fill gaps and create processes to accelerate the transformation to whole health care for veterans, both inside and outside the VA system, and the rest of the U.S. population. The resulting report presents findings and recommendations that provide a roadmap for improving health and well-being for veterans and the nation.
Keywords: Health and Medicine

Children's Environmental Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Board on Population Health and Public Health Practice, Board on Environmental Studies and Toxicology, and Board on Children Youth and Families convened a workshop in August 2022 to explore the impact of specific environmental exposures in utero, infancy, early childhood, and adolescence. Experts in epidemiology, toxicology, dose response methodology, and exposure science explored gaps in knowledge around vulnerabilities to environmental hazards as well as opportunities to inform public policy moving forward. This Proceedings of the workshop summarizes important discussions held during the virtual event and outlines recommendations for ways the Environmental Protection Agency can incorporate new research methods into its risk assessments.
Keywords: Health and Medicine; Environment and Environmental Studies

The Roles of Trust and Health Literacy in Achieving Health Equity: Public Health Institutions: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the second of three workshops, this one focusing on how health literacy best practices might affect trust in public health institutions at the state, local, tribal, and federal levels. The different contexts of trust include self-trust, trust within interpersonal relationships, trust within an organization, trust outside of an organization, and trust on a societal level, and public health institutions are reliant on trust on all of these levels to operate. This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

Roundtable on Population Health Improvement: Annual Report 2022 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Board on Population Health and Public Health Practice's Roundtable on Population Health Improvement was established in February 2013 to bring together philanthropy, community-based organizations, health care delivery, governmental public health, academia, and business in a wide-ranging dialogue about what is needed to improve health in the United States and across diverse populations. In 2022, the Roundtable on Population Health Improvement hosted workshops and webinars designed to illuminate issues of importance to leaders and policy makers, practitioners, and researchers in the health and social sectors; explore promising and innovative solutions for and approaches to population health improvement; and facilitate new and generative connections among people and organizations.
Keywords: Health and Medicine

Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme heat is a pervasive and critical hazard of climate change. While heat poses a significant threat to large swaths of the human population, it is not affecting all people or all communities equally. To explore what it takes to prevent and mitigate inequitable health impacts from extreme heat, the National Academies Environmental Health Matters Initiative (EHMI) organized a workshop on June 20-21, 2023, titled Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts. The workshop was the third in a series of EHMI events exploring the state of knowledge about climate-related health disparities. This hybrid event convened people with lived experience in communities affected by extreme heat; experts in environmental health, economic, and racial justice; climate scientists; energy specialists; and people involved in sustainable planning and disaster relief. Through presentations, shared stories, and interactive discussions, participants explored real-world challenges related to extreme heat, along with actions being pursued to prevent, adapt to, or mitigate the health consequences.
Keywords: Environment and Environmental Studies; Health and Medicine

Sponsor Influences on the Quality and Independence of Health Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Governments, philanthropic organizations, and private industry fund human health and medical research. Various funding sources might bias research so that the results are more favorable to their agents. Funders may influence investigative scope, specific questions posed, experimental design, and principal investigator appointments. Reporting, analysis, dissemination, and communication and data availability, reanalysis, and replication can also experience bias from a funding source. To explore structures, processes, and principles to ensure high-quality health research independent of sponsor influence, the National Academies Board on Population Health and Public Health Practice and the Board on Health Sciences Policy hosted a public virtual workshop in December 2022 that examined the sources of funding for health research and evidence on whether they influence the quality and outcomes of resulting health research. The workshop also discussed models, process, and principles used to protect the independence and quality of research. This Proceedings summarizes the discussions held during the workshop.
Keywords: Health and Medicine

Wastewater-based Disease Surveillance for Public Health Action - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic spurred a rapid expansion of wastewater-based infectious disease surveillance systems to monitor and anticipate disease trends in communities.The Centers for Disease Control and Prevention (CDC) launched the National Wastewater Surveillance System in September 2020 to help coordinate and build upon those efforts. Produced at the request of CDC, this report reviews the usefulness of community-level wastewater surveillance during the pandemic and assesses its potential value for control and prevention of infectious diseases beyond COVID-19. Wastewater-based Disease Surveillance for Public Health Action concludes that wastewater surveillance is and will continue to be a valuable component of infectious disease management. This report presents a vision for a national wastewater surveillance system that would track multiple pathogens simultaneously and pivot quickly to detect emerging pathogens, and it offers recommendations to ensure that the system is flexible, equitable, and economically sustainable for informing public health actions. The report also recommends approaches to address ethical and privacy concerns and develop a more representative wastewater surveillance system. Predictable and sustained federal funding as well as ongoing coordination and collaboration among many partners will be critical to the effectiveness of efforts moving forward.
Keywords: Environment and Environmental Studies; Health and Medicine

Roundtable on Genomics and Precision Health: 2022 Annual Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The members and staff of the Roundtable on Genomics and Precision Health continue to work toward their vision of realizing the full potential of health for all through genomics and precision health by bringing together diverse voices to encourage innovation and actions that foster the wide adoption of and equitable access to the benefits of genomics and precision health. During 2022, Roundtable members explored topics such as the value of and protections for genomic data and the policies surrounding them; reporting of genetics and genomics advances for both scientific audiences and the general public; workforce diversity, equity, and inclusion issues in industry; and challenges and opportunities for the adoption of genomics outside of the traditional genetics clinic.
Keywords: Health and Medicine

Attacks on Scientists and Health Professionals During the Pandemic: Proceedings of a Symposium—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Scientists and health professionals have long been targeted in connection with their professional work. Though this problem preceded the pandemic, it has emerged as a major concern, both in the United States and globally, as a result of COVID-19. Since the onset of the pandemic, scientists and health professionals have been subjected to threats and other attacks - online and offline - resulting from their efforts to combat the spread of COVID-19 with public health interventions and information. Reports of violence - carried out by numerous actors, including governments, groups, and individuals - are wide ranging and have come from all over the globe. In some cases, scientists, health professionals, and other groups have been targeted by multiple sources simultaneously, putting them at heightened risk of harm. Beginning September 1, 2022, the U.S. National Academies of Sciences, Engineering, and Medicine Committee on Human Rights hosted five webcasts examining the global problem of COVID-19-related attacks on researchers and health professionals, along with concerns regarding repression of information during the pandemic and implications for internationally protected rights. Topics included the targeting of scientists and public health professionals for providing evidence-based health information, global patterns of violence against health personnel, censorship and the right to information, science communication and human rights amid public health emergencies, and constructing a human rights framework for online health-related speech. This Proceedings of a Symposium-in Brief provides a high-level summary of the issues discussed during the series.
Keywords: Policy for Science and Technology

Advances in the Diagnosis and Evaluation of Disabling Physical Health Conditions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The U.S. Social Security Administration (SSA) provides benefits to adults and children who meet the eligibility requirements for a disability as described in Title II and Title XVI of the Social Security Act. To determine whether more accurate or precise techniques exist for determining if a previously evaluated physical impairment is either more or less severe, SSA requested the National Academies assemble a committee to review new or improved diagnostic or evaluative techniques that have become generally available within the past 30 years for cardiovascular, neurological, respiratory, hematological, and digestive conditions. The resulting report presents a summary of the evidence and information around a selected subset of diagnostic and evaluative techniques.
Keywords: Health and Medicine

Airports Responding to Public Health Emergencies: Legal Considerations - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The collapse in U.S. air traffic during the start of the COVID-19 pandemic illustrates the speed with which a severe public health emergency can devastate the air travel industry. It further illustrates how quickly an airport operator may have to react to a public health crisis. The TRB Airport Cooperative Research Program's ACRP Legal Research Digest 44: Airports Responding to Public Health Emergencies: Legal Considerations is designed to help airport sponsors and other stakeholders in the airport industry consider potential legal questions that they could confront as they address a future public health emergency.
Keywords: Transportation and Infrastructure

Engaging Community Health Workers/Youth Ambassadors to Improve Health Literacy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy, in collaboration with the HHS Office of Minority Health (OMH), hosted a workshop in April 2023 to explore the use of community health workers and youth ambassadors in promoting health literacy in their communities. Held in observation of National Minority Health Month, workshop discussions highlighted the effectiveness of including youth and young adults in community-based interventions, and lessons learned from implementing similar grant programs under the OMH Advancing Health Literacy to Enhance Equitable Community Responses to COVID-19 and the National Infrastructure for Mitigating the Impact of COVID-19 within Racial and Ethnic Minority Communities. This Proceedings of a Workshop-in Brief summarizes the discussions held during the workshop.
Keywords: Health and Medicine

The Roles of Trust and Health Literacy in Achieving Health Equity: Community Settings: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the third of three workshops to address the themes of trust and positive health equity outcomes that arise from strategic community-based organization practices. Given the historical and current reasons individuals and communities with marginalized identities have to mistrust public health communications and institutions, health literacy is essential. To bolster mutual trust, hospitals, payers, providers, and public health professionals should have the cultural competence and humility to match the health literacy needed from their patients.This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

The Roles of Trust and Health Literacy in Achieving Health Equity: Clinical Settings: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the first of three workshops to explore the positive impacts on health equity improved literacy practices in clinical settings can have. To relate and inspire confidence, physicians must communicate plainly and at the literacy level of the patient and recognize the knowledge the patient brings. Equality and equity are not the same, and treating every patient, their conditions, history, and identity, identically can interfere with trust. Diversifying the work force can facilitate better clinical practices that honor all patients. This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

Improving Access to High-Quality Mental Health Care for Veterans: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mental and behavioral health care needs of Americans, including veterans, have substantially grown over the past few decades. As the nations largest provider of mental health care, the U.S. Department of Veterans Affairs (VA) faces some of the greatest challenges in meeting the mental health care needs of its population. These challenges are exacerbated by a shrinking mental health care workforce and provider shortages in low-income and rural communities. To address these challenges, and at the request of VA, the National Academies of Sciences, Engineering, and Medicine Forum on Mental Health and Substance Use Disorders held a public workshop on Improving Access to High-Quality Mental Health Care for Veterans to explore the U.S. landscape for mental health care services, including telehealth services. The workshop considered ways to improve veterans timely access to high-quality care for mental health conditions. In particular, it explored internal and external best practices for three critical needs for mental health access (known as tripartite access in VA): urgent/crisis, engagement, and sustained access. This proceedings document summarizes discussions at the workshop.
Keywords: Health and Medicine

Population Health in Challenging Times: Insights from Key Domains: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The year 2020 presented extraordinary challenges to organizations working to improve population health - from public health agencies at all levels of government to health systems to community-based non-profit organizations responding to health-related social needs. To improve understanding of how different domains in the population health field are responding to and being changed by two major crises (racial injustice and the COVID-19 pandemic), the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine held a workshop from September 21-24, 2020, titled Population Health in Challenging Times: Insights from Key Domains. The workshop had sessions organized by themes: academic public health and population health; the social sector; health care, governmental public health; philanthropy; and cross-sector work. Each panel discussion highlighted difficulties and opportunities, both internal to the respective institutions and sectors, and at the interface with peers and partners, especially communities. This publication summarizes the presentations and panel discussions from the workshop.
Keywords: Health and Medicine